Determinação da freqüência natural de eixos utilizando o software excel - Silva, Mateus de Souza Pereira [UNESP] (2012)
This work aims to determine the first natural frequency of rotation shaft by using a basic software, Excel, and to compare it to the values obtained in laboratory. When an axle is submitted to a rotation, depending on the rotational frequency used, the axle can enter a state of resonance, in which the amplitude of vibration becomes rather high. The frequencies in which the resonance is observed depends on several parameters of the axle, including the number of concentrated masses associated to the axle. Thus, to obtain a computer program of easy use and access, which can preview the frequency of resonance of an axle in rotation with ‘n’ numbers of concentrated masses it has been studied how the frequency varies with each of these parameters. The computer program and the analyses have been made using the Rayleigh Method, which allowed the transformation of a continuous system to discrete through the theory of finite elements, which has proved that, the bigger the number of divisions of the shaft taken into consideration in the calculus of the natural frequency, the more this value gets close to the real value. The results obtained have been considered satisfactory once these have gotten close to the theoretical results expected